Art of Visualization in Building Construction: Drafting as Communication, Coordination, Regulation, and Budgeting - Wendy Hakim; Anggi Rahmad Zulfikar; Feriza Nadiar; Fajar Indra Kusuma; Desy Ratna Arthaningtyas (ULTIMART Jurnal Komunikasi Visual, 2026)
This study investigate the importance of drafting in AEC (architecture, engineering, and construction) industry. The article goes beyond seeing drafting as a technical task of producing drawings, but as a visual art, as it transform abstract ideas into visual construction knowledge. It is interpretive as drafting requires judgment to select, organise, and to communicate technical, legal, spatial, and financial information. At the same time, drafting is also a synthesis as it brings those four different forms of knowledge altogether to become a unity of coordinated visual medium. Construction industry becomes multifaceted and more dependent on digital tools. Thus, this study brings literatures review from several fields to look at how drafting works in four significant areas. Firstly, it helps diverse professionals communicate. Second, it solves coordination problems. Third, it shows legal compliance. Last, it also supports budgeting. While each of these areas has been studied on its own, few studies connect them all through the role of drafting. This study suggests that drafting is not merely a technical task, but also shapes how construction projects happen. Because of this, the paper argues that professionals in the AEC field need to better understand how drafting affects teamwork, legal processes, and financial planning. The model shown in this paper can be a platform for new research, policy, and training to understand the influence of graphical representations, such as drafting, on the physical construction of buildings.